Internalization of Harmony through Interfaith Interaction in the Kampung Toleransi Community - Pandu Hyangsewu; Hilman Taufiq Abdillah; Vina Aulia (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2023)
When religious diversity in society is not addressed wisely, it becomes a source of inter-religious conflict. The misalignment between the hope to live in harmony with the reality that occurs in society encourages an urgency to internalize values and activities to create harmony in society. So this research aims to further analyze the inter-religious interaction in the Kampung Toleransi community as a form of internalization of harmony. This research uses a qualitative approach with phenomenological methods. This research reveals that the inter-religious interaction built by Kampung Toleransi continues to be carried out and delivered culturally by various parties. So that interaction is rooted in everyday life and can realize harmony in society. The development of interfaith interaction models and strategies that apply in general can be studied in further research.